The Relationship between Efficacy and Self-Regulation with Learning Outcomes in Elementary School Mathematics - Loliyana, Loliyana; Efendi, Ujang; Hasanah, Wiwin Winawati; Hermawan, Jody Setya (Universitas Islam Negeri Raden Intan Lampung, 2022)
The problem in this research is the low mathematics learning outcomes of fourth grade elementary school students. The purpose of this study was to determine a positive and significant relationship between self-efficacy and students' mathematics learning outcomes, to determine a positive and significant relationship between self-regulation in learning and students' mathematics learning outcomes, to determine a positive and significant relationship between efficacy and self-regulation in learning with students' mathematics learning outcomes. This type of research after the fact correlation. The population is 221 students and the sample are 70 students using the technique probability sampling. Data collection techniques used observation, interviews, documentation studies and questionnaires while data analysis used correlation product moment and multiple correlation. The results showed that there was a positive and significant relationship between efficacy and self-regulation with students' mathematics learning outcomes, with a correlation coefficient of 0.7322 at the